2009
DOI: 10.1111/j.1349-7006.2009.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peptides applicable as vaccines for HLA‐A26‐positive cancer patients

Abstract: One‐fifth of the Japanese population is positive for HLA‐A26, but few peptides are available as potential cancer vaccines for HLA‐A26‐positive cancer patients. The objective of this study was to identify peptide vaccine candidates for HLA‐A26‐positive cancer patients. The HLA‐A*2601‐crossbinding activity of 24 peptides currently under clinical trial as vaccines for HLA‐A2, ‐A24, or HLA‐A3 supertype–positive cancer patients was evaluated by stabilization assay. Three peptides with HLA‐A2‐binding activity could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Dendritic cells pulsed with this peptide in a cocktail elicited responses from patients' lymphocytes responding to antigen-pulsed DC by positive ELISPOTs. Whsc2 mRNA was initially discovered to be made by gliomas and CTLs could be developed that responded towards glioma cells [39], [53]. By proteomic studies and confirmed by western blotting, Whsc2 was found to be heavily expressed in gliomas, but not in normal tissue [54].…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells pulsed with this peptide in a cocktail elicited responses from patients' lymphocytes responding to antigen-pulsed DC by positive ELISPOTs. Whsc2 mRNA was initially discovered to be made by gliomas and CTLs could be developed that responded towards glioma cells [39], [53]. By proteomic studies and confirmed by western blotting, Whsc2 was found to be heavily expressed in gliomas, but not in normal tissue [54].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first clinical trial of peptide‐based cancer vaccines for HLA‐A26 + cancer patients. The HLA‐A26 allele is found in approximately 11% of the Japanese population and includes various genotypes . The frequencies of the different HLA‐A26 genotypes in the Japanese population have been reported as follows: HLA‐A2601: 7.35%; HLA‐A2603: 2.23%; HLA‐A2603: 1.81%; HLA‐A2605: 0.07%; and HLA‐A2606: 0.01% .…”
Section: Discussionmentioning
confidence: 99%
“…One of them could be deletion or depression of the expression of HLA‐A26 molecules on the surface of cancer cells from these HLA‐A26 homogenous advanced cancer patients. PBMCs from HLA‐A26 heterogeneous advanced cancer patients were provided for in vitro determination of these 4 peptides that could induce peptide‐specific CTL activity for HLA‐A26 + cancer patients as reported previously . Their clinical stages were not as advanced as to those of the 21 patients who received PPV in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations